2012
DOI: 10.1158/1078-0432.ccr-11-2759
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of Pancreatic Neuroendocrine Tumors in Sporadic and Von Hippel-Lindau Patients

Abstract: Purpose: Von Hippel-Lindau (VHL) disease is an inherited syndrome caused by germline mutations in the VHL tumor suppressor gene, predisposing to a variety of neoplasms including pancreatic neuroendocrine tumors (PanNET). In VHL disease, PanNET probably progress according to a specific pathway of carcinogenesis. Our aim was to characterize by molecular quantitative analysis a panel of molecules implicated in the VHL pathway and in tumor progression in the PanNET of patients with VHL.Experimental Design: The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…Activating CDK4 mutations ( R24C and R24H ) that prevent inhibition by p16 INK4A increase melanoma risk [80]. Intriguingly, loss of p16 INK4A also contributes to pancreatic neuroendocrine tumours, which include islet tumours such as insulinomas [81–85]. Paradoxically, when not deleted, p16 INK4A may be overexpressed in tumours and transformed cells [86, 87].…”
Section: General Biology Of Cdkn2a/b Locus Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Activating CDK4 mutations ( R24C and R24H ) that prevent inhibition by p16 INK4A increase melanoma risk [80]. Intriguingly, loss of p16 INK4A also contributes to pancreatic neuroendocrine tumours, which include islet tumours such as insulinomas [81–85]. Paradoxically, when not deleted, p16 INK4A may be overexpressed in tumours and transformed cells [86, 87].…”
Section: General Biology Of Cdkn2a/b Locus Genesmentioning
confidence: 99%
“…In a single study, CDKN2A/B polymorphisms were not associated with AIR max , a surrogate for beta cell mass [207]. On the other hand, the contribution of p16 INK4A loss to pancreatic neuro endocrine tumour risk may imply a role in human islet cell proliferation [81–85]. …”
Section: Evidence That Human Cdkn2a/b-related Type 2 Diabetes Risk Inmentioning
confidence: 99%
“…The VHL gene is a tumor suppressor gene leading to the expression of a protein responsible for HIF degradation. Its mutation or inactivation leads to the accumulation of the HIF protein and to a "pseudohypoxic" state with enhanced transcription of specific target genes such as CA9 and GLUT1 [32]. In digestive NEN, the VHL pathway may play an important role -for example, in patients with VHL disease.…”
Section: Discussionmentioning
confidence: 99%
“…VHL is a tumor suppressor gene in VHL disease in which PanNETs are observed in 12% to 17% of cases [36]. Mutation of VHL causes disruption of the interaction between the transcription factor HIF and VHL protein, leading to constitutive HIF activation and expression of HIF targets, affecting many cellular processes such as angiogenesis and cell metabolism [37,38]. One case of a VHL mutation in our study could be considered sporadic because the mutation was observed only in the tumor and not in a non-tumor sample.…”
Section: Discussionmentioning
confidence: 99%